ANALISIS FLAVONOID DAN TANNIN DENGAN METODA MIKROSKOPI-MIKROKIMIAWI - Sri Mulyani; Toga Laksana (Majalah Obat Tradisional, 2011)
Studies have been conducted to analyze flavonoids and tannins using microscopy-microchemical methods. Materials used for the analysis of flavonoid were orange peel, sonchi leaves, and orthosiphon leaves, with N. exaltata as negative control. While guajava leaves, guazama leaves, and areca seed were used for the analysis of tannins, with ginger rhizome as negative control. The study was conducted in a way of material sliced crosswise, subsequently given the identification reagent for flavonoids (ammonia, NaOH, AlCl3, sitroborat). On the other hand, using FeCl3, fast blue salt, and prusian blue for tannins. Having examined under a microscope, the area which gave a positive reaction to the reagent used, indicate the test materials contained compounds that were analyze. The results showed that this microscopy-microchemical method can be used to analyze the presence of flavonoids / tannins in the test material. Presence of flavonoid compounds will give yellow color with ammonia, NaOH, AlCl3, sitroborat reagent, while blue to black for the tannins with FeCl3, red with fast blue salt, and blue with prusian blue.